JURNAL ILMU KEHUTANAN : Assessment of Vegetation Cover Status in Dry Lands of The Sudan Using Social and Terrestrial Data - Mohammed Hamed Mohammed (Fakultas Kehutanan UGM, 2016)
The current study was conducted in 2015 in Bara Locality, North Kordofan, Sudan. The study area has experienced recurrent drought spells since 1970s of the past century.